Acceptability of Suitably Designed Garments for Nursing Mothers in Ondo City Metropolis, Nigeria - Esther Oseyemi Akinyotu; Fatimat Damilola Alao (International Journal of Home Economics, Hospitality and Allied Research, 2022)
This study was designed to compare the appropriateness of the usual and suitably designed garments for nursing mothers in Ondo City metropolis. The study adopted descriptive survey design and research and development (R&D) methods. Three hundred and sixty (360) respondents were randomly selected from nine immunization clinic centers in Ondo City Metropolis. Two research questions and one null hypotheses (tested at 0.05 level of significance) guided the study. Specifically the study sought to document the challenges encountered by nursing mothers in using the usual garments for breastfeeding, and to identify features of an appropriate garment that can be suitably designed for breastfeeding. The instrument used for data collection was Breast-Feeding Mothers Opinion Questionnaire. The data were analyzed using frequencies, percentages, mean and standard deviation to answer the research questions. Null hypotheses were tested at 0.05 level of significance. The study revealed that nursing mothers encounter challenges in using the usual garments for breastfeeding. These challenges include, but are not limited to, unavailability of the desired design for nursing garments, inappropriate time or place to express breastfeeding, inability to understand figure type and faults so as to choose suitable and flattering styles, inability to find nursing garments that fit to the desired design, among others. The study also found out garments that are good for breastfeeding. It was recommended that dress makers take a proactive stance to produce comfortable, convenient and beautiful designs for nursing mothers.